Investigation of the actin scavenging system in pre-eclampsia - Tannetta, D; Redman, C; Sargent, I (2014)
Objectives Cell injury releases actin, the most abundant cell protein. Gelsolin and vitamin D binding protein (VDBP) together depolymerise and clear cell-free actin. Impaired actin clearance is associated with several diseases and correlates with clinical outcome. The actin scavenging system was investigated in pre-eclampsia (PE), a procoagulant and proinflammatory state with placental and vascular damage. Study design Plasma gelsolin and actin free VDBP (AFVDBP) were measured in PE (early onset <33 weeks; late onset ≥36 weeks), matched normal pregnant (normP) and non-pregnant (nonPr) women, using commercially available ELISAs. Longitudinal samples from normP and women who subsequently developed PE were also analysed. Results Plasma gelsolin fell during pregnancy (p = 0.0002), with a concomitant rise in actin-free VDBP (p < 0.001). Gelsolin concentrations were only significantly lower in established PE (p < 0.05) when compared to non-pregnant controls. Conclusions We have shown that the components of the actin clearance system, gelsolin and AFVDBP, are altered in normal pregnancy and further changes occur in established PE, suggesting depleted actin clearance in PE. Whether this is a cause or consequence of PE pathophysiology requires further investigation. © 2013 The Authors.